COVID-19 and Other Pleiotropic Actions of Vitamin D Proceedings from the 5th International Conference "Vitamin D-minimum, maximum, optimum" - Pludowski, Pawel (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
It is a great pleasure to provide you this Special Issue of Nutrients related to the 5th International Conference "Vitamin D-Minimum, Maximum, Optimum", under the auspices of the European Vitamin D Association (EVIDAS). The conference and the forthcoming papers serve as an international forum for the presentation and discussion of current basic and clinical research in the field of vitamin D. Organizing this subsequent Special Issue was truly challenging, given that vitamin D has recently been shown by prestigious medical journals to be an epiphenomenon that coincides with diseases, and that the correction of vitamin D deficits has limited clinical meaning. On the other hand, it was recognized that vitamin D deficiency is a global health problem with potential negative consequences on health, welfare, and morbidity during growth and adulthood, therefore influencing healthcare services worldwide. Thus, due to mutually exclusive conclusions, it was essential to discuss and share scientific reports and evidence demonstrating both the benefits and lack thereof in relation to human health. Prof. Dr. Pawel Pludowski Guest Editor